Clinical implications of anticoagulant oral therapy in elderly patients with hip fracture. - Cosseddu, Fabio; Ipponi, Edoardo; Perna, Luigi; Paterni, Simone; Capanna, Rodolfo; Andreani, Lorenzo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim:Proximal femur fractures (PFFs) are among the most common fractures, especially in the elderly population. A PFF often represents a life-changing event. Their dramatic effects are attributable not only to the massive hemorrhages caused by the fracture, but also to the high risk of dramatic complications. These risks are supposed to be even higher for patients under oral anticoagulant treatment. In this study we evaluated how oral anticoagulant therapy effected patient’s prognosis. Methods:Ours was a case-control review of over-65 patients treated surgically for proximal femur fractures between 2013 and 2019. Cases were divided in 2 groups depending if they were (Group A) or were not (Group B) under oral anticoagulant therapy at the moment of hospitalization. Results:200 cases were included in our study: 100 in Group A and 100 in Group B. Surgical delay was significantly higher for cases under oral anticoagulant treatment compared to the other cases. Group A cases were transfused with a significantly higher frequency and with more blood units compared to Group B (p=0.0300; p=0.013). Combined cardiological and vascular complications occurred in 21 cases (10.5%), being significantly more common in Group A (16) than Group B (5), as testified by a chi-square test (P=0.011). Conclusions:Cases under oral anticoagulant therapy are frail patients with a higher risk to develop massive hemorrhages after an hip fracture. For this reason, it is mandatory to achieve an early stabilization of patient’s clinical conditions and then perform surgery as soon as possible.